Systematic Literature Review Informing LIS Professionals on Embedding Librarianship Roles - Abrizah, Abdullah; Inuwa, S.; Afiqah-Izzati, N. (Elsevier, 2016)
Purpose Embedded librarianship currently receives renewed interest worldwide, seeks to bring the library and the librarian to users in their work environment. This paper identifies and documents embedding librarianship roles as reported in the Library and Information Science (LIS) literature.